2012
DOI: 10.1007/s00508-012-0239-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and management of group B streptococcal colonization during pregnancy in Africa

Abstract: Group B streptococcal infections are a leading cause of neonatal morbidity and mortality. Maternal microbiological screening during pregnancy and intrapartum antimicrobial treatment of maternal group B streptococcus (GBS) colonization constitutes an effective prevention strategy to reduce early neonatal invasive disease due to GBS in the European and North American setting. Data on the prevalence of GBS colonization in pregnancy and incidence of neonatal invasive GBS disease are very limited for low-income reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…In Morocco, one study found asymptomatic carriage rate of 23.3% [3]. Similar or higher rates were found in Southern Africa [10,[12][13][14]. Our study, which is the first on this topic to be conducted in the DRC, had similar results.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In Morocco, one study found asymptomatic carriage rate of 23.3% [3]. Similar or higher rates were found in Southern Africa [10,[12][13][14]. Our study, which is the first on this topic to be conducted in the DRC, had similar results.…”
Section: Discussionsupporting
confidence: 78%
“…As stated earlier, the relatively high rate of vaginal colonization with GBS and its pathogenicity have justified the implementation of screening, prevention, and treatment strategies [2,4,7,12]. Clinical practice guidelines have advocated intrapartum antibiotherapy to prevent GBS infection of the neonate, but the expected prevention of late-onset neonatal infection does not seem to be supported by conclusive data [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4 In low-income settings screening and IAP for prevention of invasive neonatal disease are mostly not implemented due to limitations in resources and infrastructure. 5 GBS remain fully susceptible to penicillin as well as to most blactams. [6][7][8][9] However, there are some worrisome reports on reduced penicillin susceptibility in GBS.…”
Section: Introductionmentioning
confidence: 99%
“…In industrialized countries prenatal screening in pregnant women and intra-partum antibiotic prophylaxis (IAP) have been widely established and successfully reduced the incidence of newborn morbidity and mortality related to S. agalactiae 1 2 . In low income settings recto-vaginal colonization rates with S. agalactiae in pregnant women are similar 3 ; however, screening and IAP for prevention of invasive neonatal disease is mostly not implemented due to limitations in resources and infrastructure. Vaccination of pregnant women is an alternative prevention strategy that proved effective for other neonatal infectious diseases (i.e.…”
mentioning
confidence: 99%